ANALYSIS OF THE POTENTIAL AND IMPACT OF CREATIVE ECONOMICS ON REGIONAL DEVELOPMENT IN KETE KESU VILLAGE, SANGGALANGI DISTRICT, TORAJA DISTRICT - Muhajir, Humaidid; Safitra, Nur; Mutmainnah, Inayatul; Ramadani Salam, Eka Fitra (Multifinance, 2023)
The potential of the Kete Kesu Tourism Object and the creative economy as an element of regional original income This study aims to find out what the potential of the creative economy is in Kete Kesu Village, Sanggalangi District, North Toraja Regency, and to determine the impact of the creative economy on development in Kete Kesu Village, Sanggalangi District, North Toraja Regency. The type of research used is quantitative research. The data collection method used in this study is observation, interview, and documentation, where the author sees the situation directly in the field. The research results obtained by researchers indicate that the creative economic potential in Kete Kesu Village, Sanggalangi District, North Toraja Regency, has very broad potential. It can be involved in the business that is mostly carried out, which is trending handicrafts, carvings, and souvenirs, as well as trending woven fabrics. Therefore, we can see that in Kete Kesu Village, it has very broad potential for developing the creative economy, and the second goal is the impact of the creative economy on development in Kete Kesu Village, Sanggalangi District, North Toraja Regency, namely to have a positive impact on development. Specifically, the existence of development makes tourists interested in visiting. This has increased the creative economy in the village.